Temperature measurements from treatment and control plots of a passive warming experiment at a cushion bog on Tierra del Fuego, Argentina - Pancotto, Veronica Andrea (2021)
We conducted our study in a cushion bog dominated by Astelia pumila on Tierra del Fuego, Argentina (54.972° S, 66.734° W). We experimentally investigated how a cushion bog plant community responded to elevated surface temperature conditions. We installed a year-round passive warming experiment using semicircular plastic walls that raised average near-surface air temperatures between 0.4°C and 0.7°C (at the three of ten treatment plots which were equipped with temperature sensors). We conducted chamber gas flux measurements to characterize differences in carbon dioxide exchange dynamics between the treatment and control plots.